Design and development of system to control, synchronize and coordinate multiple high-performance microvalves - Ishanova, B. (Recent Contributions to Physics, 2014)
The innate nature of humans to manipulate and thereby control forces of nature has traditionally stirred efforts aimed at the development of modern technology. With that view in mind, this thesis details the design of a mechanism which would aid the performance of physical tasks in a number of industries. More specifically, the development of a system to control, synchronize and coordinate multiple high performance microvalves wirelessly is proposed in this study. The goal of this article is to perform a system which can control microvalves by sending a specific command from a Graphical User Interface. This controller allows the controlling ON and OFF switching of the devices wirelessly. The development system plays a crucial role in the oil and gas industry. Quite recently, considerable attention has been paid to automatic functions and its growth potential appears unlimited. It will be extremely efficient to provide automatic functions to optimize system performance. Some limitations to control pressure or flow automatically can be used to balance requirement conditions which ensure that flow or pressure will not exceed a desired rate. An implication of these findings helps to reduce energy consumption and therefore minimize the risk of noise.